ANALISIS SISTEM PERAWATAN ASET OPERASIONAL MEDIS RSUD JAYAPURA PROVINSI PAPUA - , Siti Nahiya Patiran ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Medical equipment is one factor that plays an importan role in health service to the community. Sustainable health services need to be supported with equipment that is always in a condition ready to use and can be used with either. The research was conducted at the Regional General Hospital Jayapura, Papua Province. Importance performance analysis is use to analyze the determinants of success of asset maintenance activities, while SWOT analysis is used to develop maintenance strategies and the priority level of the existing strategy. The results showed that: 1) an analysis of asset maintenance systems of medical devices indicates that there is still a gap between the factors that are considered important to the performance of maintenance in the regional general hospitals in papua. Factors that lies in the first guadrant IPA analysis (factors that are important but the performance is not good) are: (attention to asset maintenance program of medical devices that are routinely scheduled, attention to asset maintenance program of medical devices are scheduled at regular intervals, level existence of standard operating procedure care, such as medical instruments, non-medical, or otherwise, confidence in the examination/evaluation on the condition of assets medical devices, process supervise the implementation of asset care medical devices are functioning properly, confidence in the observation and treatment efforts utilization of medical devices to function properly, level of professionalism in the utilization of human resources and asset care medical devices, level of transparancy costs associated with asset maintenance of medical devices). 2) According to SWOT analysis over asset maintenance system of medical instruments in RSUD Jayapura, it depicts a highly favorable situation, where the organization has the strength and oppertunity, therefore they can take adventage of existing opportunities. The stratefy necessary to paply is to boast aggressive growth (SO strategy or strength-opportunity).